Implikasi Pelaporan Kinerja Guru PAI terhadap Profesionalitas Pembelajaran pada Sekolah Dasar di Aceh Besar - Rosmawar Rosmawar (Tadabbur: Jurnal Peradaban Islam, 2020)
The teacher's performance will describe his ability to carry out the task, to achieve the goals that have been set. The success rate of teacher performance in addition to showing the teacher's mastery of his competence is also influenced by several factors, both originating from his personality characteristics and environmental factors, such as teacher work discipline. The purpose of this study was to determine the content of reporting on the performance of PAI teachers and the responses of PAI teachers at elementary schools in Aceh Besar. This research was conducted by using a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews, observation and documentation. The results showed that the contents of reporting on the performance of PAI teachers at elementary schools in Aceh Besar included lesson plans designed at the beginning of the semester, the implementation of face-to-face learning in the classroom, assessing learning outcomes as a benchmark for students' ability to understand learning, guide and train students whether it is done during the teaching and learning process, or through remedial and enrichment, and learning methods used to facilitate teachers in the teaching and learning process in the classroom. The response (response) of PAI teachers at elementary schools in Aceh Besar to the content of their reports is based on the abilities or competencies possessed by a teacher, as well as support from the principal for the content of their performance reports, as well as an attitude of accepting what results have been realized in the reporting content in school. The implication of the content of performance reporting on the professionalism of PAI teacher learning at SD in Aceh Besar is that a professional PAI teacher must have mastery of the material to be explained to students in class, master competency standards and basic competencies to make it easier for teachers to map the learning provided, develop learning materials which is taught effectively by combining with the surrounding environment, utilizing technological tools as competitiveness in the digital era, and using interesting media to make it easier for students to understand learning.